Peningkatan Daya Saing Produk Songkok Lokal Lamongan Melalui Program Pemberdayaan Ekonomi Kreatif - Sutatik Herawati; Aris Sunarya; Sri Roekminiati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The songkok industry in Lamongan has quite a large economic potential, but still faces various challenges in increasing competitiveness, especially in facing increasingly tight market competition. Some of the main obstacles found are lack of innovation, limited access to wider markets, and low utilization of technology in production and marketing. This study aims to explore strategies to increase the competitiveness of local songkok products through a creative economic empowerment program using the Chambers Theory perspective. The research method used is a qualitative approach with data collection techniques in the form of in-depth interviews, field observations, and literature studies. Data analysis was carried out descriptively qualitatively with three main stages, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that the creative economic empowerment program plays a significant role in improving craftsmen's skills, encouraging innovation in design, and expanding the marketing reach of songkok products. By applying analysis based on Chambers Theory, this empowerment contributes to increasing power within (craftsmen's confidence and awareness), power to (individual capacity to innovate and develop businesses), power with (collaboration between craftsmen in the community), and power over (ability to face competition and external constraints). Based on these results, it can be concluded that empowering the creative economy is an effective strategy in increasing the competitiveness of Lamongan songkok products. Therefore, close cooperation is needed between the government, the artisan community, and the private sector in order to create a sustainable creative industry environment.